2013
DOI: 10.17762/ijnpme.v2i01.13
|View full text |Cite
|
Sign up to set email alerts
|

Modified Golomb-Rice Algorithm for Color Image Compression

Abstract: The memory required to store the color image is more. We have reduced the memory requirements using Golomb-rice algorithm. Golomb-rice algorithm consists of the following two steps. In Golomb-Rice algorithm the first step is to compress the image using discrete wavelet transform. By using DWT compression the 8 × 8 image is converted into m × n sub-windows and it is converted into raster file format for producing m × n-1 differential data. Encoding is done by using Golomb-Rice coding.  After encoding, the proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The second problem is future link prediction; it says that if you have been given a graph at time t0, your task is to predict the edges which will be added at time t1. Future link prediction can be further classified into two categories: periodic, where the link is expected on time, and the other is non-periodic, where the link is predicted based on a particular snapshot of the network [15]. The link prediction problem is very complex in itself.…”
Section: Gt0(ve): Topology At Time T=t0 Gt1(v'e'): Topology At Time T=t1mentioning
confidence: 99%
“…The second problem is future link prediction; it says that if you have been given a graph at time t0, your task is to predict the edges which will be added at time t1. Future link prediction can be further classified into two categories: periodic, where the link is expected on time, and the other is non-periodic, where the link is predicted based on a particular snapshot of the network [15]. The link prediction problem is very complex in itself.…”
Section: Gt0(ve): Topology At Time T=t0 Gt1(v'e'): Topology At Time T=t1mentioning
confidence: 99%
“…Friedman and Schuster [20] enhanced the Data Mining-Decision Tree algorithm for better privacy and data accuracy. Simi, Nayaki, and Elayidom [21] addressed business and research-oriented fields, discussing the use of k-anonymization to protect privacy.…”
Section: Meyerson and Williamsmentioning
confidence: 99%
“…A solid-state room temperature terahertz source is developed using standard microelectronics fabrication process steps [ 32 ]. The details of the design and the development of the source are reported elsewhere [ [14] , [15] , [16] , [17] , [18] ]. The position of the source with respect to the detector is varied for getting the optimum penetration depth.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Here they have developed a room temperature terahertz source for the study and reported elsewhere [ [14] , [15] , [16] , [17] , [18] ]. The radiation coming out from the waveguide embedded THz-solid-state source is incident on the human respiratory tract and THz thermographs are generated and an image analyzer is placed for analyzing the output.…”
Section: Introductionmentioning
confidence: 99%